1980
DOI: 10.1038/288705a0
|View full text |Cite
|
Sign up to set email alerts
|

Ability of kallikrein to generate angiotensin II-like pressor substance and a proposed ‘kinin–tensin enzyme system’

Abstract: Pig pancreatic kallikrein liberates kallidin from kininogen, whereas trypsin releases bradykinin. Recently, both kallikrein and trypsin have been reported to convert inactive plasma renin to active renin. However, we found that at pH 6.0, trypsin generated an angiotensin II-like pressor substance from human plasma protein in the absence of converting enzyme. This has been isolated and found to have the same amino acid composition as angiotensin II. Thus, in vitro trypsin can directly liberate both the depresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

1984
1984
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 12 publications
1
30
0
2
Order By: Relevance
“…The mechanism might involve activation by trypsin of an enzyme capable of so doing, such as tonin. 12 Conversely, activation of renin-known to be relatively abundant in the uterine wall 13 ' 14 and to increase considerably during pregnancy 14 -could be the first step of another such mechanism. This would require the Ang I generated to be converted to Ang II, a process heretofore considered unlikely, given the low Ang I converting enzyme activity ascribed to the rat uterus.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism might involve activation by trypsin of an enzyme capable of so doing, such as tonin. 12 Conversely, activation of renin-known to be relatively abundant in the uterine wall 13 ' 14 and to increase considerably during pregnancy 14 -could be the first step of another such mechanism. This would require the Ang I generated to be converted to Ang II, a process heretofore considered unlikely, given the low Ang I converting enzyme activity ascribed to the rat uterus.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Arakawa et al (7) demonstrated that trypsin generated angiotensin II (AngII) from human plasma protein in the absence of angiotensin converting enzyme (ACE) at weakly acidic pH 7.0). Our previous report showed that pancreatic cancer tissues had higher trypsinogen expression and higher AngII concentrations than other solid tumors, such as HCC and colorectal cancer (8).…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer cells express trypsinogen that converts to trypsin at pH 5.5 [25]. Furthermore, mast cells that migrate into gastric cancer tissues express tryptase.…”
Section: -1 the Mechanism Of Secretion Of Tgf-β By Gastric Cancer Cellsmentioning
confidence: 99%